2018
DOI: 10.1002/ceas.12096
|View full text |Cite
|
Sign up to set email alerts
|

The Lived Experiences of Men in a Master's Counseling Program

Abstract: Using phenomenological methodology, the authors explored the experiences of 11 men in a master's‐level counseling program. Participants described the challenges and advantages of being a minority in number, being in a relational environment, and having an awareness of a patriarchal system. These findings suggest the importance of counselor educator awareness of the unique barriers male students face.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Like Crockett and colleagues (2018) and Vela, Fisk, et al (2019), we followed Moustakas's (1994) procedures for data collection and analysis. These procedures were (a) selecting a phenomenon of interest: Latinx college students' lived experiences with their high school counselors; (b) bracketing our research assumptions and values; (c) collecting data from individuals with experiences with high school counselors; (d) analyzing participants' experiences for commonalities; (e) writing a description of what participants experienced; and (f) describing the essence of participants' lived experiences with their high school counselors (Crockett et al, 2018).…”
Section: Research Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Like Crockett and colleagues (2018) and Vela, Fisk, et al (2019), we followed Moustakas's (1994) procedures for data collection and analysis. These procedures were (a) selecting a phenomenon of interest: Latinx college students' lived experiences with their high school counselors; (b) bracketing our research assumptions and values; (c) collecting data from individuals with experiences with high school counselors; (d) analyzing participants' experiences for commonalities; (e) writing a description of what participants experienced; and (f) describing the essence of participants' lived experiences with their high school counselors (Crockett et al, 2018).…”
Section: Research Proceduresmentioning
confidence: 99%
“…Data Collection. Interviews are a method of data collection in phenomenology to gain insight into participants' lived experiences (Crockett et al, 2018;Moustakas, 1994;Young, 2017). The eight Latinx undergraduate students participated in both individual and focus group interviews for our study during the fall semester of 2021.…”
Section: Research Proceduresmentioning
confidence: 99%
“…We followed Moustakas’ (1994) procedures for qualitative data collection and analysis: (a) selecting a phenomenon of interest: Latine college students’ lived experiences with their high school counselors as related to CCW; (b) bracketing our research assumptions, beliefs, and values; (c) collecting data from individuals with experiences with high school counselors; (d) analyzing participants’ experiences for commonalities; (e) writing a description of what participants experienced with high school counselors as related to CCW; and (f) describing the essence of participants’ lived experiences with their high school counselors as related to CCW (Crockett et al., 2018; Vela, Guerra, et al., 2023).…”
Section: Research Proceduresmentioning
confidence: 99%
“…Research on master’s‐level students found that age, political, spiritual, and religious factors predicted perceived psychological safety and appreciation of differences (Giordano, Bevly, Tucker, & Prosek, 2018); multicultural personality, not ethnic identity, predicted multicultural counseling competency (Fietzer, Mitchell, & Ponterotto, 2018); and helping professionals from different fields did not vary in need for social distance from mental illness (Tillman et al, 2018). Qualitative investigations included those on men’s experiences (Crockett, Elghoroury, Popiolek, & Wummel, 2018) and microaggressions toward lesbian, gay, bisexual, transgender, queer or questioning, plus other identities (LGBTQ+) students (Bryan, 2018) in master’s degree programs. Contributions to the understanding of doctoral students included development of African American mothers (Appling, Haskins, & Daigle, 2018), social class microaggressions (O’Hara & Cook, 2018), and international students’ development of professional identity (Kuo, Woo, & Washington, 2018).…”
Section: Understanding Stakeholdersmentioning
confidence: 99%